Transvascular Implantation of an Implantable Cardioverter-Defibrillator in a Patient Who has Undergone One-and-a-Half Ventricle Repair - Yang, Pil-Sung; Park, Je Wook; Lee, Yong-Joon; Kim, Dong-Jun; You, Seng Chan; Park, Dong Hyuk; Uhm, Jae-Sun; Kim, Nam Kyun (Korean circulation journal, 2015)
Implantable cardioverter-defibrillator (ICD) therapy is acknowledged as a valid treatment method for the effective prevention of sudden cardiac death, which is a major cause of mortality in adult congenital heart disease patients. But ICD implantation by the conventional transvascular approach is not always possible in patients who have undergone palliative surgery due to congenital and structural heart disease. Here, we report a case in which an ICD was transvascularly implanted in an arrhythmogenic right ventricular cardiomyopathy patient who had undergone a one-and-a-half ventricle repair.